Cervical screening and the aftermath of childhood sexual abuse: are clinical staff trained to recognise and manage the effect this has on their patients?. Issue 13 (8th October 2013) - Walker, Judith; Allan, Helen T
<x xml:space="preserve">Abstract</x> Aims and objectives To evaluate the training needs and awareness of childhood sexual abuse amongst clinical staff taking cervical screening samples in one inner city primary care trust. Background Studies exploring sexual abuse and nonparticipation in cervical screening have demonstrated that women can experience re‐traumatisation if care during examinations is insensitive to their particular needs. Design This was a mixed methods, service evaluation in three phases. Methods A literature review, a questionnaire to cervical screening staff in an inner city primary care trust and a focus group of four staff drawn from questionnaire respondents to explore themes raised in the questionnaire data. Results Data analysis of both quantitative and qualitative data showed that clinical staff underestimated the frequency of childhood sexual abuse although they were aware of the difficulties and reluctance some women experience undergoing gynaecological examinations. When women did disclose childhood sexual abuse or when staff suspected a history of childhood sexual abuse, staff reported feeling unsure of how they should proceed. There was no support or clinical supervision, and unmet training needs were identified. Conclusions Nurses expressed anxiety around the potential of the screening test to cause more harm than good and at their inability to provide more help than listening. Staff wanted support and further training after completing their cervical screening training course to assist in their provision of sensitive care to patients who have experienced childhood sexual abuse. Relevance to clinical practice Whilst our results cannot be generalised to a wider population, they may be meaningful for the community of cervical screening takers. We argue that screening staff require further training and professional support (clinical supervision) to increase their confidence when providing safe and sensitive practice for childhood sexual abuse survivors. If staff feel more confident and competent when responding to disclosure of childhood sexual abuse in screening situations, women who have experienced childhood sexual abuse might participate in the screening programme more readily.